Strong Amplification of ELF/VLF Signals in Space Using Neutral Gas Injections From a Satellite Rocket Engine. Issue 2 (23rd February 2021) - Bernhardt, Paul A.; Bougas, William C.; Griffin, Michael K.; Watson, Chris; Langley, Richard B.; Howarth, Andrew D.; James, H. Gordon; Siefring, Carl L.; Perry, Gareth W.; Huba, Joseph. D.; Moore, Robert C.; Cohen, Morris. B.; et al.
Abstract: The first demonstration of rocket exhaust driven amplification (REDA) of whistler mode waves occurred on May 26, 2020 by transferring energy from pickup ions in a rocket exhaust plume to EM waves. The source of coherent VLF waves was the Navy NML Transmitter at 25.2 kHz located in LaMoure, North Dakota. The topside ionosphere at 480 km altitude became an amplifying medium with a 60 s firing of the Cygnus BT‐4 engine. The rocket engine injected exhaust as a neutral cloud moving perpendicular to field lines that connected the NML transmitter to the VLF Radio Receiver Instrument (RRI) on e‐POP/SWARM‐E. Charge exchange between the ambient O + ions and the hypersonic water molecules in the exhaust produced H2 O + ions in a ring‐beam velocity distribution. The 25.2 kHz VLF signal from NML was amplified by 30 dB for a period 77 s as observed by the RRI. Simultaneously, preexisting coherent ELF waves at 300 Hz were amplified by 50 dB during and after the Cygnus burn. Extremely strong coherent emissions and quasiperiodic bursts in the 300–310 Hz frequency range lasted for 200 s after the release. The excitation of an ELF whistler cavity may have lasted even longer, but the orbit of the SWARM‐E/e‐POP moved the RRI sensor away from the wave emission region. The amplified 300 Hz ELF waves may have gained even more energy by cyclotron resonance with radiation belt electrons as they were ducted between geomagnetic‐conjugate hemispheres. Plain Language Summary: The rocket exhaust driven amplification (REDA) technique AMPLIFIES whistler waves from existing ground transmitters rather than trying to GENERATE large amplitude whistler waves from space‐based transmitters. REDA employs liquid propulsion systems to inject water vapor into the topside ionosphere. The H2 O molecules move at the vector sum of the orbit and the rocket‐exhaust velocities yielding between 4 and 10 km/s. The water molecules are stream perpendicular to the magnetic field, B, charge exchange with ambient O+ ions and gyrate around B. Whistler waves that propagate through this activated plasma region are greatly amplified as energy is transferred from the ions to waves. Internationally, 21 ground VLF transmitters are available for REDA tests. The strong whistler waves from REDA can be used to interact with the population of radiation belt electrons. Key Points: Rocket exhaust driven amplification creates Intense Whistler Waves at ULF and VLF frequencies for interactions with Radiation Belts Transmissions from the NML VLF transmitter operating at 25.2 kHz were amplified by 20–30 dB as measured by the SWARM‐E satellite Whistler waves that propagate through an activated plasma region are greatly amplified as energy is transferred from the ions to waves